Integration of Ethanol Processor and CO2 Absorption to Produce Hydrogen for Fuel Cell - Yaneeporn Patcharavorachot; Kidakarn Sangduan; Pimporn Ponpesh; Suttichai Assabumrungrat; Amornchai Arpornwichanop (My University, 2014)
Ethanol is considered to be a promising candidate for hydrogen source. Hydrogen-rich gas with less impurity level of carbon monoxide and carbon dioxide is required for fuel cell applications. In a conventional ethanol processor, CO can be removed by water gas-shift reactors, followed by a preferential oxidation unit. Since a high content of CO2 may degrade the efficiency of fuel cell systems, the removal of CO2 should be included in the ethanol processor to separate CO2 from the synthesis gas. In this study, the thermodynamic analysis of hydrogen production from the integration of ethanol reforming process and CO2 absorption unit is performed. The purity of H2, efficiency of CO2 removal and heat consumption are key factors to be analyzed with regard to different key parameters. The result indicates that the H2 purity of 97 mol.% can be reached when the CO2 absorption unit is included in the ethanol steam reforming. In addition, it is found that the CO2 removal can be improved with increases of amine concentration, number of absorber and stripper stages, whereas increase of inlet gas temperature show the opposite trend. However, high energy demand is unavoidable when a number of absorber and stripper stages increase.
Keywords: Catalysts for Methane Reforming